Stem Cells: Injectable Peptide Decorated Functional Nanofibrous Hollow Microspheres to Direct Stem Cell Differentiation and Tissue Regeneration (Adv. Funct. Mater. 3/2015). (January 2015) - Zhang, Zhanpeng; Gupte, Melanie J.; Jin, Xiaobing; Ma, Peter X.
<x xml:space="preserve">Abstract</x> P. X. Ma and colleagues report the novel functional nanofibrous hollow microspheres (FNF‐HMS) for tissue regeneration on page 350. Peptide decorated FNF‐HMS are shown to directly guide stem cells to form cartilage and bone, respectively, circumventing the use of the expensive and unstable growth factors. FNF‐HMS can therefore serve as an advanced injectable carrier platform for various therapeutic applications. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>